2013
DOI: 10.3390/su5093615
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the United Nations Conference on Sustainable Development (Rio +20) Discourse Using an Ability Expectation Lens

Abstract: Abstract:The United Nations Conference on Sustainable Development (Rio +20) was hosted in Rio de Janeiro, Brazil, from June 20-22, 2012, 20 years after the first Earth Summit, with the intention of creating solutions to current global environmental issues. In this paper we present the results of an analysis of academic and newspaper articles that covered the Rio +20 summit, using an ability expectation lens. Articles were collected from academic databases such as EBSCO, as well as from newspapers such as the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Social entities from individuals to societies as a whole [14] cherish numerous abilities (e.g., competitiveness, ability to consume, being productive, being able to live in harmony with nature), not just body-related abilities. Related to the topic of this call for papers, ability expectations have been described for education for sustainable development [17], waste and footprint [19], energy [20], Rio+20 discourse [21], ecohealth [22], ability privilege [18] and why disabled people are invisible as stakeholders in water discourses [23]. Indicators and other performance measures all exhibit ability expectations [17].…”
Section: Analytical Framework Of Ability Studiesmentioning
confidence: 99%
“…Social entities from individuals to societies as a whole [14] cherish numerous abilities (e.g., competitiveness, ability to consume, being productive, being able to live in harmony with nature), not just body-related abilities. Related to the topic of this call for papers, ability expectations have been described for education for sustainable development [17], waste and footprint [19], energy [20], Rio+20 discourse [21], ecohealth [22], ability privilege [18] and why disabled people are invisible as stakeholders in water discourses [23]. Indicators and other performance measures all exhibit ability expectations [17].…”
Section: Analytical Framework Of Ability Studiesmentioning
confidence: 99%
“…However it’s less clear why they failed. Sometimes documents are covered or not based on whether they fit a certain agenda of the newspaper and its publisher [ 38 ]. However given that aging and physical activity by themselves are covered extensively in the newspapers including problems linked to aging this reason seems not to fit.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that successfully implemented social programs correlate well with sustainable development goals to eliminate poverty and provide peace and prosperity for all (Giribabu Dandabathula et al 2018). However, the aims of inclusive development cannot be achieved without addressing the needs of disadvantaged people (Noga and Wollbring 2013). Social instability, injustice, and social hazards can Adm. Sci.…”
Section: Introductionmentioning
confidence: 99%